Development of coordination abilities in children with intellectual disabilities using exercises on neurotrainers - Naumenko, Y.V.; Artemenko, E.P. (Theory and Practice of Physical Culture, 2026)
The purpose of the study is to substantiate the methodology for developing motor and coordination abilities in children with intellectual disabilities of secondary school age using neuro-exercisers. The data from our study: suggest that the developed methodology for developing coordination abilities using neuro-exercisers is effective. This conclusion is based on the statistically significant results of the control tests